2020
DOI: 10.1002/lio2.358
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological characteristics of surgical tissue from primary vs recurrent chronic rhinosinusitis with nasal polyposis patients

Abstract: Objective The histopathological characteristics of primary vs recurrent nasal polyps in patients with chronic rhinosinusitis with nasal polyps (CRSwNP) have not been studied comprehensively. Identification of these features may be helpful for prognostication, postoperative management, and consideration of novel eosinophil‐targeting biologic therapy. This study investigates the histopathological differences in primary vs recurrent CRSwNP tissue. Methods Patients undergoing endoscopic sinus surgery for CRSwNP we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…The current research aimed to evaluate cellular, epithelial and stromal inflammatory indicators in cases with primary and recurrent chronic nasal polyposis. Despite a variety of inflammatory markers being used in this study after FESS, mucosal eosinophilia and basal membrane thickness [BMT] showed a statistically significant difference between primary and recurrent chronic polyposis in rhinosinusitis cases, however, eosinophilia showed weak significant values [P = 0.044] and eosinophil aggregates [P = 0.049] which was similar to Donnell et al [12] who found that increasing eosinophils have more eosinophil aggregates [P < 0.001]. The presence of eosinophilia in primary and recurrent CRSwNP were studied extensively more than eosinophilic aggregates [7,[13][14] .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The current research aimed to evaluate cellular, epithelial and stromal inflammatory indicators in cases with primary and recurrent chronic nasal polyposis. Despite a variety of inflammatory markers being used in this study after FESS, mucosal eosinophilia and basal membrane thickness [BMT] showed a statistically significant difference between primary and recurrent chronic polyposis in rhinosinusitis cases, however, eosinophilia showed weak significant values [P = 0.044] and eosinophil aggregates [P = 0.049] which was similar to Donnell et al [12] who found that increasing eosinophils have more eosinophil aggregates [P < 0.001]. The presence of eosinophilia in primary and recurrent CRSwNP were studied extensively more than eosinophilic aggregates [7,[13][14] .…”
Section: Discussionsupporting
confidence: 81%
“…Eosinophils are the most prevalent inflammatory cells in nasal polyp tissues, except in cases of cystic fibrosis. Steroids diminish eosinophilic infiltration of the upper airway by decreasing eosinophil viability [7][8][9][10][11][12][13][14][15] . The increase in eosinophils in chronic recurrent polyposis can be explained because These cells release mediators such as eosinophil-derived neuro-toxin and eosinophil cationic protein and can also synthesize a number of regulatory molecules such as transforming growth factor β and interleukin-4, which can directly or indirectly contribute to the further recruitment and activation of eosinophils capable of causing cellular injury and tissue damage [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Following studies used structured HP reporting looking to distinguish histological markers in order to stratify subtypes and discern the puzzling pathophysiological mechanisms in CRS [31][32][33]. The association of HP findings with clinical features of CRS and CRS categories was investigated recently using 99 patients and 13 variables [31].…”
Section: Figure 3 -Nasal Polyp Area With Profound Epithelial Erosionsmentioning
confidence: 99%
“…The HP aspect of the polyp specimens was typified by Donell et al [33] in primary vs. recurrent CRSwNP patients undergoing ESS. The authors did not find any disparity between primary and recurrent CRSwNP for eosinophilic infiltrated tissue, but in recurrent CRSwNP cases mucin was quite often inclined to presents eosinophil aggregates compared to primary CRSwNP.…”
Section: Figure 3 -Nasal Polyp Area With Profound Epithelial Erosionsmentioning
confidence: 99%
See 1 more Smart Citation